Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s11914-018-0422-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Coupling Between Bone Marrow Adipose Tissue and Hematopoiesis

Abstract: An important physiological function of MAT may be to provide an expandable/contractible fat depot, which is critical for minimization of energy requirements for sustaining optimal hematopoiesis. Because the energy requirements for storing fat are negligible compared to those required to maintain hematopoiesis, even small reductions in hematopoietic tissue volume to match a reduced requirement for hematopoiesis could represent an important reduction in energy cost. Such a physiological function would require ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 74 publications
0
28
0
Order By: Relevance
“…Based on this model, metabolic coupling between mesenchymal and hematopoietic cells in bone marrow regulates MAT levels. Thus, the well‐established inhibitory effects of chronic alcohol consumption on hematopoiesis may be responsible for increased MAT here and in rodent models (Heermans, ; Siggins et al., ; Turner et al., ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Based on this model, metabolic coupling between mesenchymal and hematopoietic cells in bone marrow regulates MAT levels. Thus, the well‐established inhibitory effects of chronic alcohol consumption on hematopoiesis may be responsible for increased MAT here and in rodent models (Heermans, ; Siggins et al., ; Turner et al., ).…”
Section: Discussionmentioning
confidence: 94%
“…Osteoblasts and bone marrow adipocytes originate from the same bone marrow mesenchymal stem cells, and in vitro studies suggest that, at high concentrations, alcohol decreases osteoblast number by modulating the differentiation program of stem cells to form adipocytes at the expense of osteoblasts (Chen et al., ; Wezeman and Gong, ). However, there is also evidence that osteoblasts and marrow adipocytes are regulated independently (Turner et al., ). Specifically, we have shown that neither pathological increases in marrow adiposity following hypophysectomy in rats (Menagh et al., ) nor absence of marrow adiposity in mice with loss‐of‐function mutations in c‐kit signaling (Iwaniec and Turner, ; Keune et al., ) influence the skeletal response to bone anabolic or catabolic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantity of bMAT in distal femur metaphysis is context-dependent and, as recently reviewed (35), influenced by numerous factors, including skeletal site, age, food availability, and housing temperature. Increased bMAT occurs with extremes in energy availability; obesity and rapid weight loss each result in increased bMAT.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that other cell types in bone also play a role in bone biology, such as neuron cells. More recently, adipocytes in the BM space have been demonstrated to exert impacts on osteogenesis , hematopoiesis and tumor survival . However, IVI has not been employed for investigation of fluorescence labeled neuron cells and adipocytes in bone.…”
Section: Outlook and Concluding Remarksmentioning
confidence: 99%